2014
DOI: 10.1186/s40555-014-0042-2
|View full text |Cite
|
Sign up to set email alerts
|

A global overview on the diet of the dice snake (Natrix tessellata) from a geographical perspective: foraging in atypical habitats and feeding spectrum widening helps colonisation and survival under suboptimal conditions for a piscivorous snake

Abstract: Background: The dice snake (Natrix tessellata Laurenti, 1768) is generally considered to be a fully or partially piscivorous freshwater snake species. The aim of the study was to make the first global overview on the taxonomy and geographical distribution of the species based on own observations, available databases and the special literature. Results: Besides freshwaters, N. tessellata turned out to hunt also in marine and terrestrial habitats predating on at least 29 and 15 species, respectively. On the basi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Vol. : (0123456789) (Weiperth et al 2014). Research has demonstrated that in heavily urbanized areas, dice snakes can adjust their diet according to the prevalent prey, as seen in their exclusive consumption of invasive fish species in the Danube (Maier et al 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Vol. : (0123456789) (Weiperth et al 2014). Research has demonstrated that in heavily urbanized areas, dice snakes can adjust their diet according to the prevalent prey, as seen in their exclusive consumption of invasive fish species in the Danube (Maier et al 2023).…”
Section: Discussionmentioning
confidence: 99%
“…We did detect a potential signal of phylogenetic biascolubrid species had significantly larger urban niche hypervolumes than elapids. However, this bias may genuinely reflect colubrid snakes' ability to colonise novel habitats (Ivanov 2000;Rodda et al 1992;Weiperth et al 2014), rather than a sampling bias. Colubrids are arguably the most successful radiation of snakes on the planet, boasting the widest phylogenetic diversity and geographic distribution of any snake family (Figueroa et al 2016;O'Shea 2018;Pincheira-Donoso et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Natrix tessellata is typically olivegreen or brown in colour with four rows of square-like black blotches along the body, although not all individuals are marked in this way. The species feeds primarily on fish and amphibians (Hutinec & Mebert, 2011;Weiperth et al, 2014), and inhabits both freshwater and saltwater environments such as lakes and shorelines (Speybroeck et al, 2016).…”
mentioning
confidence: 99%